Manufacturing method of positive electrode plate

JP2025034318APending Publication Date: 2025-03-13TOYOTA BATTERY CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023140628
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-31
Publication Date
2025-03-13

AI Technical Summary

Benefits of technology

【0018】 本発明によれば、正極結着剤の添加量を抑えながら正極合剤の剥離強を高くできる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025034318000001_ABST
    Figure 2025034318000001_ABST
Patent Text Reader

Abstract

To provide a manufacturing method of a positive electrode plate, capable of enhancing a peeling strength of a positive electrode mixture while suppressing the adding amount of a positive electrode binding agent.SOLUTION: A manufacturing method of a positive electrode plate comprising a positive electrode base material and a positive electrode mixture layer provided at least one surface of the positive electrode base material, comprises: a positive electrode mixture paste manufacturing step of manufacturing a positive electrode mixture paste for forming the positive electrode mixture layer; and an applying step of applying the positive electrode mixture paste. The positive electrode mixture paste manufacturing step comprises: a first mixing step S21 of mixing a positive electrode active material, part of the whole adding amount of a PVdF as a positive electrode binding agent to be added, and an NMP as a positive electrode solvent to manufacture a first mixing paste; a second mixing step S22 of adding and mixing an NMP solution and a positive electrode conductive agent to the first mixing paste to manufacture a second mixing paste; and a third mixing step S23 of adding and mixing the remain of the whole adding amounts of the PVdF to the second mixing paste to manufacture the positive electrode mixture paste.SELECTED DRAWING: Figure 5
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for manufacturing a positive electrode plate. [Background technology]

[0002] Electric vehicles and hybrid vehicles include non-aqueous secondary batteries as their power sources. A lithium ion secondary battery, which is an example of a non-aqueous secondary battery, includes an electrode body in which a positive electrode plate, a negative electrode plate, and a separator are laminated. The positive electrode plate includes a positive electrode base material and a positive electrode mixture. The positive electrode mixture includes a positive electrode active material, a positive electrode conductive agent, and a positive electrode binder. A positive electrode mixture paste, which is a precursor of the positive electrode mixture, includes a positive electrode active material, a positive electrode conductive agent, a positive electrode binder, and a positive electrode solvent. As shown in Patent Document 1, polyvinylidene fluoride (PVdF) or the like is sometimes used as the positive electrode binder. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2012-134023 A Summary of the Invention [Problem to be solved by the invention]

[0004] In high-power non-aqueous secondary batteries, it is necessary to reduce the internal resistance of the battery. A positive electrode binder such as PVdF is necessary to improve the adhesion between the positive electrode active materials and the peel strength between the positive electrode mixture and the positive electrode substrate. On the other hand, an increase in the positive electrode binder increases the internal resistance because the positive electrode binder itself has high resistance. For this reason, in high-power non-aqueous secondary batteries, it is necessary to increase the peel strength without increasing the amount of positive electrode binder added.

[0005] In Patent Document 1, the use of two types of active materials with different average particle diameters and specific surface areas is proposed as a method for increasing the peel strength with the same composition. Patent Document 1 is restricted by the use of two types of active materials. In addition, Patent Document 1 states that if the particles of the two types of active materials are not uniformly dispersed in the electrode, unevenness in the peel strength will occur. [Means for solving the problem]

[0006] A manufacturing method of a nonaqueous secondary battery for solving the above problems is a manufacturing method of a positive electrode plate including a positive electrode base material and a positive electrode mixture layer provided on at least one surface of the positive electrode base material, the manufacturing method including a positive electrode mixture paste manufacturing step of manufacturing a positive electrode mixture paste that forms the positive electrode mixture layer, and a coating step of coating the positive electrode mixture paste, the positive electrode mixture paste manufacturing step including a first kneading step of manufacturing a first kneaded paste by kneading a positive electrode active material, a part of a total amount of a positive electrode binder to be added, and a part of a total amount of a positive electrode solvent to be added, a second kneading step of manufacturing a second kneaded paste by adding the remainder of the total amount of the positive electrode solvent and a positive electrode conductive agent to the first kneaded paste and kneading them, and a third kneading step of manufacturing the positive electrode mixture paste by adding the remainder of the total amount of the positive electrode binder to the second kneaded paste and kneading them.

[0007] In the above-mentioned method for producing a positive electrode plate, the positive electrode binder is preferably polyvinylidene fluoride (PVdF). In the above-mentioned method for producing a positive electrode plate, the positive electrode solvent is preferably an NMP (N-methyl-2-pyrrolidone) solution.

[0008] According to the above configuration, in the second kneading step, the amount of the positive electrode binder added is suppressed, so that it is possible to prevent the molecular chain of the positive electrode binder from being cut when the positive electrode conductive agent is dispersed. In the third kneading step, the remaining positive electrode binder is added and kneaded to obtain the required peel strength.

[0009] The positive electrode mixture layer can increase the peel strength by increasing the amount of the positive electrode binder added. On the other hand, the positive electrode binder has a high resistance itself, so that the internal resistance is high. In the present invention, the adhesion between the positive electrode active materials is also increased, and the positive electrode binder can be sufficiently dissolved in a positive electrode solvent such as NMP. Therefore, the peel strength of the positive electrode active material can be further increased while suppressing the amount of the positive electrode binder added. In addition, since the positive electrode mixture paste has an appropriate viscosity, problems such as filter clogging and streaking during the coating process can be suppressed.

[0010] In the method for producing a positive electrode plate, it is preferable that the positive electrode active material contains a chlorine component, and the chlorine content of the positive electrode active material is 0.002 mass % or more and 0.02 mass % or less with respect to the mass of the positive electrode active material.

[0011] According to the above configuration, in the first kneading step, the chlorine component contained in the positive electrode active material attracts the positive electrode binder such as PVdF to the positive electrode active material, so that the positive electrode binder can be entangled with the positive electrode active material. If the chlorine content in the positive electrode active material is less than 0.002 mass%, the effect of entanglement of the positive electrode binder and the active material cannot be sufficiently obtained. If the chlorine content is more than 0.02 mass%, the viscosity of the positive electrode mixture paste becomes too high, causing filter clogging, streaking, etc. in the coating step.

[0012] In the method for producing a positive electrode plate, the amount of excess lithium contained in the positive electrode active material is preferably 0.07 mass % or more and 0.12 mass % or less with respect to the mass of the positive electrode active material.

[0013] According to the above-mentioned configuration, the excess lithium forms long-chain double bonds by dehydrofluorination reaction, which makes it difficult for the positive electrode binder to move from the surface of the active material. If the amount of excess lithium is less than 0.07% by mass, the peel strength becomes insufficient. If the amount of excess lithium is more than 0.12% by mass, the viscosity of the positive electrode mixture paste becomes too high, which causes filter clogging and streaking during the coating process.

[0014] In the above-mentioned method for manufacturing a positive electrode plate, it is preferable that a solubility index calculated by (DCR of the positive electrode solvent in the positive electrode mixture paste after the third kneading step) / (DCR of the positive electrode solvent in the second kneaded paste before the start of the third kneading step) is 1.19 or more.

[0015] The solubility index of the positive electrode solvent increases as the positive electrode binder dissolves. By controlling the solubility index to be 1.19 or more, a positive electrode mixture paste in which the positive electrode binder is sufficiently dissolved can be produced after the third kneading step.

[0016] In the above-mentioned method for producing a positive electrode plate, it is preferable that an adhesion index calculated by (DCR of the positive electrode active material in the positive electrode mixture paste) / (DCR of all components of the positive electrode active material, the positive electrode conductive agent, and the positive electrode solvent in the positive electrode mixture paste) is 0.70 or more and 0.80 or less.

[0017] By controlling the adhesion index to be 0.70 or more and 0.80 or less, the dissolution state of the positive electrode binder can be made appropriate, which means that the peel strength can be maintained while preventing problems such as filter clogging and streaking during the coating process. Effect of the Invention

[0018] According to the present invention, the peel strength of the positive electrode mixture can be increased while reducing the amount of the positive electrode binder added. [Brief description of the drawings]

[0019] [Figure 1] FIG. 1 is a perspective view of a lithium ion secondary battery. [Diagram 2] FIG. 2 is a perspective view showing the electrode body in an expanded state. [Diagram 3] FIG. 3 is a process diagram illustrating a method for producing a lithium ion secondary battery. [Figure 4] FIG. 4 is a process diagram illustrating a method for manufacturing a positive electrode plate as a comparative example of the embodiment. [Diagram 5]FIG. 5 is a process diagram illustrating a method for producing a positive electrode plate in the embodiment. [Figure 6] FIG. 6 is a diagram showing an equivalent circuit in which a resistance component (R) and a pseudo capacitance (C) are connected in parallel, which are formed in the paste. [Figure 7] FIG. 7 is a diagram showing examples and comparative examples of the lithium ion secondary battery according to the embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0020] Hereinafter, one embodiment of the present invention will be described with reference to FIGS. [Lithium-ion secondary battery] As shown in FIG. 1, a lithium ion secondary battery 10, which is an example of a non-aqueous secondary battery, includes a case 11 and an electrode assembly 20. The case 11 has a flat, bottomed, rectangular outer shape with an opening on the upper side. The case 11 contains the electrode assembly 20 and a non-aqueous electrolyte. The case 11 includes a pair of side walls 11A disposed opposite each other. The lid 12 closes the opening of the case 11. By attaching the lid 12, the case 11 forms a sealed rectangular parallelepiped battery container.

[0021] The lid 12 is provided with a positive external terminal 13A and a negative external terminal 13B. The positive electrode side current collector 20A, which is the end of the electrode body 20 on the positive electrode side, is electrically connected to the positive electrode external terminal 13A via a positive electrode side current collector 14A. The negative electrode side current collector 20B, which is the end of the electrode body 20 on the negative electrode side, is electrically connected to the negative electrode external terminal 13B via a negative electrode side current collector 14B. The lid 12 is provided with an injection port 15 for injecting a nonaqueous electrolyte. The shapes of the external terminals 13A and 13B are not limited to those shown in FIG. 1 and may be any shape.

[0022] [Electrode body 20] As shown in FIG. 2, the electrode body 20 is a flat wound body formed by winding a laminate in which a positive electrode plate 21 and a negative electrode plate 24 are stacked with a separator 27 interposed therebetween. As an example, the laminate is stacked in the order of the separator 27, the negative electrode plate 24, the separator 27, and the positive electrode plate 21. The positive electrode plate 21, the negative electrode plate 24, and the separator 27 are stacked such that their respective longitudinal directions coincide with the longitudinal direction D1. The electrode body 20 has a structure in which the positive electrode plate 21 and the negative electrode plate 24 stacked with the separator 27 sandwiched therebetween are wound around a winding axis L1 extending along the width direction D2 of the band shape.

[0023] 2, the electrode body 20 is stacked such that a separator 27 is disposed between a positive electrode plate 21 and a negative electrode plate 24. The stacking direction is perpendicular to a plane including the longitudinal direction D1 and the width direction D2.

[0024] [Positive plate 21] The positive electrode plate 21 includes a positive electrode substrate 22 and a positive electrode mixture layer 23. The positive electrode substrate 22 is a foil-shaped metal made of aluminum or an aluminum alloy. The positive electrode mixture layer 23 is provided on each of two surfaces of the positive electrode substrate 22 that face in opposite directions. The positive electrode substrate 22 includes a positive electrode-side uncoated portion 22A at one end in the width direction D2 where the positive electrode mixture layer 23 is not formed and the positive electrode substrate 22 is exposed. In the positive electrode substrate 22, the positive electrode-side uncoated portion 22A includes opposing portions that are pressed against each other in a wound body state to form a positive electrode-side current collecting portion 20A.

[0025] The positive electrode mixture layer 23 includes a positive electrode active material, a positive electrode conductive agent, and a positive electrode binder. The positive electrode mixture paste, which is a precursor of the positive electrode mixture layer 23, further includes a positive electrode solvent. An example of the positive electrode solvent is an NMP (N-methyl-2-pyrrolidone) solution, which is an example of an organic solvent.

[0026] The positive electrode active material is a lithium-containing composite metal oxide capable of absorbing and releasing lithium ions, which are charge carriers in the lithium-ion secondary battery 10. The positive electrode active material releases lithium ions during charging and absorbs lithium ions during discharging. The lithium-containing composite oxide is an oxide containing lithium and a metal element other than lithium. The metal element other than lithium is at least one selected from the group consisting of nickel, cobalt, manganese, vanadium, magnesium, molybdenum, niobium, titanium, tungsten, aluminum, and iron contained in the lithium-containing composite oxide as iron phosphate.

[0027] For example, lithium-containing composite oxides include lithium cobalt oxide (LiCoO 2 ), lithium nickel oxide (LiNiO 2 ), lithium manganate (LiMn 2 O 4 For example, the lithium-containing composite oxide is a ternary lithium-containing composite oxide (NCM) containing nickel, cobalt, and manganese, such as lithium nickel cobalt manganese oxide (LiNiCoMnO 2 For example, the lithium-containing composite oxide is lithium iron phosphate (LiFePO 4 ).

[0028] The positive electrode active material contains a chlorine component. The chlorine content of the positive electrode active material is preferably 0.002% by mass or more with respect to the mass of the positive electrode active material. The chlorine content is preferably 0.02% by mass or less with respect to the mass of the positive electrode active material. By setting the chlorine content in this range, the positive electrode mixture paste can be made to have an appropriate viscosity. If the chlorine content of the positive electrode active material is less than 0.002% by mass, the effect of entanglement of the positive electrode binder and the active material cannot be sufficiently obtained. If the chlorine content is more than 0.02% by mass, the viscosity of the positive electrode mixture paste becomes too high, causing filter clogging and streaking during the coating process. The filter clogging refers to a phenomenon in which the powder of the positive electrode binder remaining dissolved in the positive electrode solvent clogs the filter.

[0029] The positive electrode active material further contains excess lithium. The excess lithium is, for example, lithium hydroxide (LiOH) that is inevitably contained in the positive electrode active material. For example, the amount of excess lithium contained in the positive electrode active material is preferably 0.07% by mass or more with respect to the mass of the positive electrode active material. In addition, the amount of excess lithium is preferably 0.12% by mass or less with respect to the mass of the positive electrode active material. When the positive electrode binder acts on the alkali content of the excess lithium, a long chain double bond is formed by a dehydrofluorination reaction, so that the positive electrode binder is difficult to move from the active material surface. If the amount of excess lithium is less than 0.07% by mass with respect to the mass of the positive electrode active material, the peel strength of the positive electrode mixture layer 23 to the positive electrode substrate 22 becomes insufficient. If the amount of excess lithium is more than 0.12% by mass with respect to the mass of the positive electrode active material, the viscosity of the positive electrode mixture paste becomes too high, and filter clogging, streaking, etc. occur in the coating process.

[0030] The positive electrode conductive agent may be, for example, carbon black such as acetylene black (AB) or Ketjen black, carbon fiber such as carbon nanotube (CNT) or carbon nanofiber, or graphite. The positive electrode binder may be, for example, at least one selected from the group consisting of polyvinylidene fluoride (PVdF), polyvinyl alcohol (PVA), and styrene butadiene rubber (SBR). In this embodiment, polyvinylidene fluoride (PVdF) is used as the positive electrode binder.

[0031] The positive electrode plate 21 may have an insulating layer at the boundary between the positive electrode uncoated portion 22A and the positive electrode mixture layer 23. The insulating layer contains an inorganic component having insulating properties and a resin component functioning as a binder. The inorganic component is at least one selected from the group consisting of powdered boehmite, titania, and alumina. The resin component is at least one selected from the group consisting of PVdF, PVA, and acrylic.

[0032] [Negative plate 24] The negative electrode plate 24 includes a negative electrode substrate 25 and a negative electrode mixture layer 26. The negative electrode substrate 25 is a foil-shaped metal made of copper or a copper alloy. The negative electrode mixture layer 26 is provided on each of two surfaces of the negative electrode substrate 25 that face in opposite directions. The negative electrode substrate 25 includes a negative electrode side uncoated portion 25A in which the negative electrode mixture layer 26 is not formed and the negative electrode substrate 25 is exposed at an end portion located opposite the positive electrode side uncoated portion 22A in the width direction D2. In the negative electrode side uncoated portion 25A, facing portions are pressed against each other in a wound body state to form the negative electrode side current collecting portion 20B.

[0033] The negative electrode mixture layer 26 includes a negative electrode active material, a negative electrode conductive agent, a negative electrode thickener, and a negative electrode binder. The negative electrode mixture paste, which is a precursor of the negative electrode mixture layer 26, further includes a negative electrode solvent. An example of the negative electrode solvent is water. The negative electrode active material is a material capable of absorbing and releasing lithium ions. The negative electrode active material absorbs lithium ions during charging and releases lithium ions during discharging. For example, carbon materials such as graphite, non-graphitizable carbon, graphitizable carbon, and carbon nanotubes are used as the negative electrode active material. The negative electrode active material may be a composite particle in which graphite particles are coated with an amorphous carbon layer.

[0034] The negative electrode conductive agent may be, for example, the same as the positive electrode conductive agent. The negative electrode thickener may be, for example, carboxymethyl cellulose (CMC). CMC also functions as a dispersant for dispersing the negative electrode active material in the negative electrode mixture paste. The negative electrode binder may be, for example, at least one selected from the group consisting of PVdF, PVA, and SBR.

[0035] [Separator] The separator 27 prevents contact between the positive electrode plate 21 and the negative electrode plate 24, and retains a nonaqueous electrolyte between the positive electrode plate 21 and the negative electrode plate 24. When the electrode body 20 is immersed in a nonaqueous electrolyte, the nonaqueous electrolyte permeates the separator 27 from the ends toward the center.

[0036] The separator 27 is a nonwoven fabric made of polypropylene, etc. As the separator 27, for example, a porous polymer membrane such as a porous polyethylene membrane, a porous polyolefin membrane, a porous polyvinyl chloride membrane, an ion-conductive polymer electrolyte membrane, etc. can be used.

[0037] [Nonaqueous electrolyte] The non-aqueous electrolyte is a composition in which a supporting salt is contained in a non-aqueous solvent. The non-aqueous solvent is, for example, one or more materials selected from the group consisting of propylene carbonate, ethylene carbonate, diethyl carbonate, dimethyl carbonate, and ethyl methyl carbonate. The supporting salt is, for example, LiPF 6 , LiBF 4 , LiClO 4 , LiAsF 6 , LiCF 3 SO 3 , LiC 4 F 9 SO 3 , LiN(CF 3 SO 2 ) 2 , LiC(CF 3 SO 2 ) 3 The non-aqueous electrolyte solution is added with a film-forming agent, which may be, for example, lithium bis(oxalato)borate (LiBOB).

[0038] [Method of manufacturing lithium ion secondary battery 10] 3, the method for manufacturing the lithium-ion secondary battery 10 includes steps S1 to S4. Step S1 is a source process including a positive plate manufacturing process for manufacturing a positive plate 21 and a negative plate manufacturing process for manufacturing a negative plate 24.

[0039] The positive electrode plate manufacturing process includes a positive electrode mixture paste manufacturing process for manufacturing a positive electrode mixture paste, and a positive electrode mixture paste application process for applying the positive electrode mixture paste to the positive electrode substrate 22. The process further includes a positive electrode mixture layer forming process for drying the positive electrode mixture paste to form the positive electrode mixture layer 23, and a positive electrode mixture layer pressing process for pressing the positive electrode mixture layer 23 to adjust the thickness.

[0040] In the positive electrode mixture paste application process, the positive electrode mixture paste is applied by a die coater unit. In general, the die coater unit includes a die and a nozzle provided in the die. The positive electrode mixture paste is supplied to the die and ejected from the nozzle onto the positive electrode substrate 22. As a result, the positive electrode mixture paste is applied to the positive electrode substrate 22.

[0041] The negative electrode plate manufacturing process includes a negative electrode mixture paste manufacturing process for manufacturing a negative electrode mixture paste, and a negative electrode mixture paste application process for applying the negative electrode mixture paste to the negative electrode substrate 25. The process further includes a negative electrode mixture layer forming process for drying the negative electrode mixture paste to form the negative electrode mixture layer 26, and a negative electrode mixture layer pressing process for pressing the negative electrode mixture layer 26 to adjust the thickness. The negative electrode mixture paste is also applied to the negative electrode substrate 25 by a die coater unit.

[0042] Step S2 is an electrode assembly manufacturing process in which the electrode assembly 20 is manufactured using the positive electrode plate 21, the negative electrode plate 24, and the separator 27. In step S2, the separator 27, the negative electrode plate 24, the separator 27, and the positive electrode plate 21 are first stacked in this order from the inner periphery side. The stack in this stacking order is wound around a winding core to form a wound body. The winding core is then pulled out from the wound body.

[0043] Thereafter, the electrode body 20 is pressed flat in the wound state. Next, the positive electrode uncoated portion 22A is pressed to form the positive electrode current collector 20A. Similarly, the negative electrode uncoated portion 25A is pressed to form the negative electrode current collector 20B. Through the above procedure, the electrode body 20 is manufactured.

[0044] Step S3 is an accommodation step for accommodating the electrode body 20 in the case 11. In step S3, the positive electrode side current collecting part 20A is electrically connected to the positive electrode external terminal 13A via the positive electrode side current collecting member 14A. The negative electrode side current collecting part 20B is electrically connected to the negative electrode external terminal 13B via the negative electrode side current collecting member 14B. After the electrode body 20 is accommodated in the case 11, the upper opening of the case 11 is closed by the lid 12.

[0045] Step S4 includes a drying step of drying the electrode body 20 housed in the case 11, and a liquid injection step of injecting a non-aqueous electrolyte solution. After that, the lithium ion secondary battery 10 is manufactured through an aging step and an initial charging step.

[0046] [Positive electrode mixture paste manufacturing process] As shown in Fig. 4, the positive electrode mixture paste manufacturing process according to the present embodiment is a reference example in which a positive electrode conductive agent, a positive electrode solvent, a positive electrode binder, and a positive electrode active material are kneaded in a kneading step S11 to manufacture a positive electrode mixture paste. That is, in the kneading step S11, all the components are kneaded at once. The kneading step S11 may include a kneading step. Thereafter, the positive electrode plate 21 is manufactured through a positive electrode mixture paste coating step, a positive electrode mixture layer forming step, and a positive electrode mixture layer pressing step.

[0047] As shown in FIG. 5, the positive electrode mixture paste manufacturing process according to this embodiment includes a first kneading step S21, a second kneading step S22, and a third kneading step S23. In the first kneading step S21, the positive electrode active material, the positive electrode binder, and a part of the total amount of the positive electrode solvent added are kneaded to produce a first kneaded paste. Here, the amount of the positive electrode binder added in the first kneading step S21 is a part of the total amount that should be added. The chlorine content of the positive electrode active material is 0.002 mass% or more and 0.02 mass% or less with respect to the mass of the positive electrode active material. The positive electrode binder is attracted to the positive electrode active material by the action of the chlorine component, so that the positive electrode binder becomes easily entangled. Whether the positive electrode binder is sufficiently entangled with the positive electrode active material can be managed by the adhesion index described later.

[0048] In addition, the positive electrode binder attracted to the positive electrode active material by the action of chlorine undergoes a dehydrofluorination reaction with excess lithium to form a long-chain double bond, which makes the positive electrode binder less likely to move from the surface of the positive electrode active material, thereby ensuring the peel strength between the positive electrode active materials.

[0049] In the second kneading step S22, the remainder of the total amount of the positive electrode solvent and the positive electrode conductive agent are added to the first kneaded paste and kneaded to produce a second kneaded paste. This disperses the positive electrode conductive agent. The second kneaded paste does not contain the total amount of the positive electrode binder. Therefore, in the second kneading step S22, it is possible to prevent the molecular chain of the positive electrode binder from being cut when the positive electrode conductive agent is dispersed. When dispersing the positive electrode conductive agent, strong stirring is required, and if the total amount of the positive electrode binder is added at this time, molecular chain cuts of the positive electrode binder will occur.

[0050] In the third kneading step S23, the remaining positive electrode binder is added to the second kneaded paste and kneaded to thoroughly dissolve the positive electrode binder, thereby producing a positive electrode composite paste, which is the third kneaded paste. This provides the required peel strength. The dissolution state of the positive electrode binder can be controlled by a solubility index, as described below.

[0051] [Solubility index and adhesion index] The above-mentioned solubility index and adhesion index can be obtained by a slurry analysis system provided by Hioki E.E. Corporation. In the slurry analysis system, a measurement electrode is inserted into the second kneaded paste before the start of the third kneading process 23 and into the positive electrode composite paste after the third kneading process 23, an AC voltage is applied to each paste, and the impedance is measured from the current response at that time. Specifically, the paste is placed in an electrode cell (SA9001), and the electrode cell is set in a test fixture (SA9002) for measurement. Then, the CSV file acquired by the measurement software (SA2633) is analyzed by the analysis software (SA2632) to acquire the DC resistance components DCR and Rratio of each substance (positive electrode solvent, positive electrode conductive agent, positive electrode active material).

[0052] As shown in FIG. 6, at this time, an equivalent circuit is formed in the paste in which a resistance component (R) and a pseudocapacitance (C) are connected in parallel. In this embodiment, an RC parallel circuit of each material, a positive electrode active material, a positive electrode conductive agent, and a positive electrode solvent, is arranged in series. In FIG. 6, the DC resistance component of the positive electrode solvent is R1, and the pseudocapacitance component is CPE1. In addition, the DC resistance component of the positive electrode conductive agent is R2, and the pseudocapacitance component is CPE2. Furthermore, the DC resistance component of the positive electrode active material is R3, and the pseudocapacitance component is CPE3.

[0053] In this embodiment, DCR (direct current resistance) is the direct current resistance component of each material (positive electrode solvent (R1), positive electrode conductive material (R2), positive electrode active material (R3)) in the equivalent circuit of the paste. The unit is Ω.

[0054] In this embodiment, the solubility index is the Rratio (resistance ratio) of the positive electrode active material, and is the ratio of the DCR of the positive electrode active material to the total DCR (R1+R2+R3).

[0055] In this embodiment, the dissolution index by the cathode solvent DCR is defined as follows: Solvent index = (DCR of the positive electrode solvent in the positive electrode mixture paste after the third kneading step 23) / (DCR of the positive electrode solvent in the second kneaded paste before the start of the third kneading step 23) ≧ 1.19 The positive electrode solvent DCR increases as the resistance increases due to the dissolution of the positive electrode binder in the positive electrode solvent. If the solubility index is less than 1.19, the positive electrode binder is not completely dissolved in the positive electrode solvent, and sufficient peel strength cannot be obtained.

[0056] In the present embodiment, the adhesion index, which is the positive electrode active material Rratio in the positive electrode composite paste that has been subjected to the third kneading step S23, is defined as follows. Adhesion index = (DCR of positive electrode active material in positive electrode mixture paste) / (DCR of all components of positive electrode active material, positive electrode conductive material, and positive electrode solvent in positive electrode mixture paste) =0.70 or more, 0.80 or less The adhesion index changes with the change in the positive electrode active material DCR. When the positive electrode binder is entangled in the positive electrode active material, the resistance of the positive electrode active material itself increases, making it difficult for electrons to flow, but this makes it easier for electrons to flow to the positive electrode conductor in the positive electrode mixture paste. As a result, it is estimated that the DCR of the positive electrode active material decreases. It can be estimated that the lower the adhesion index, the more firmly the positive electrode binder is entangled with the positive electrode active material. When the adhesion index is 0.7 or less, it becomes too difficult for electrons to move relative to the positive electrode active material, and the internal resistance becomes too high. Also, when the adhesion index is 0.8 or more, sufficient peel strength cannot be obtained.

[0057] Comparative Examples 1 to 7 and Examples 1 to 5 of the present invention will be described below with reference to FIG. The lithium ion secondary batteries 10 according to Comparative Examples 1 to 7 and Examples 1 to 5 were manufactured according to the manufacturing process shown in FIG.

[0058] Here, for the positive electrode mixture paste in the positive electrode plate 21, in Comparative Examples 1 and 2, a kneading step S11 was performed in which a positive electrode conductive agent, a positive electrode solvent, a positive electrode binder, and a positive electrode active material were kneaded at once (see FIG. 4). In contrast, in Comparative Examples 3 to 7 and Examples 1 to 5, a first kneading step S21 to a third kneading step S23 were performed (see FIG. 5).

[0059] In addition, the chlorine content contained in the positive electrode active material was measured for Comparative Examples 1 to 7 and Examples 1 to 5. The chlorine content was measured as follows. 10 g of the positive electrode active material powder dried at 110° C. for 1 hour was weighed, put into 100 ml of ion-exchanged water, and heated at 100° C. for 1 hour to elute the chlorine contained in the positive electrode active material into the ion-exchanged water. After cooling, the aqueous solution from which the solid components of the positive electrode active material were removed using filter paper was subjected to chlorine content measurement by ion chromatography. The amount of chlorine contained in the positive electrode active material was determined by this method.

[0060] The amount of excess lithium was measured for Comparative Examples 1 to 7 and Examples 1 to 5. The amount of excess lithium was measured by adding a predetermined amount (e.g., 1 g) of the positive electrode active material to pure water, stirring for a certain period of time (e.g., 30 minutes), and then subjecting the weight of each component of the lithium compound dissolved in the pure water to neutralization titration with hydrochloric acid.

[0061] The solvent index based on the positive electrode solvent DCR was calculated by (DCR of the positive electrode solvent in the positive electrode mixture paste after the third kneading step 23) / (DCR of the positive electrode solvent in the second kneaded paste before the start of the third kneading step 23).

[0062] The adhesion index was calculated by (DCR of the positive electrode active material in the positive electrode mixture paste) / (DCR of all components in the positive electrode mixture paste: the positive electrode active material, the positive electrode conductive agent, and the positive electrode solvent).

[0063] In Comparative Examples 1 and 2, the solvent index was measured before and after the kneading step S11 shown in Fig. 4. For the measurement of DCR, a slurry analysis system provided by Hioki E.E. Corporation was used.

[0064] In FIG. 7, the paste viscosity is defined as follows: ×: Cannot be applied due to high viscosity △: Lower viscosity 〇: Same as before.

[0065] Filter clogging is defined as follows: The period until the conventional filter (Comparative Example 1) reaches the end of its life is taken as the filter clogging level of "1." If the filter life is shorter than the conventional filter, the level is less than "1," and if the filter life is longer than the conventional filter, the level is greater than "1."

[0066] ×: 0.8 or less △: greater than 0.8 and less than 1.0 ◯: 1.0 or more (filter life is equal to or greater than that of the conventional filter (Comparative Example 1)).

[0067] Furthermore, the peel strength is defined as follows: The peel strength is set to 1.00 with Comparative Example 1 as the standard (1.0). ×: 0.9 or less △: greater than 0.9 and less than 1.1 〇:1.1 or higher.

[0068] Comparative Example 1 Comparative Example 1 is a conventional manufacturing method. In Comparative Example 1, when manufacturing a positive electrode mixture paste, a positive electrode conductive agent, a positive electrode solvent, a positive electrode binder, and a positive electrode active material are charged at once and kneaded (see FIG. 4). This leads to molecular chain scission of the positive electrode binder PVdF during kneading. In addition, the amount of residual chlorine is 0.001 mass %, which is smaller than 0.002 mass %, and the positive electrode binder is not sufficiently entangled with the positive electrode active material. Therefore, the adhesion index is 0.85, which exceeds 0.80. As a result, the paste viscosity and the filter clogging are both good results of "◯", but the peel strength is "△".

[0069] Comparative Example 2 In Comparative Example 2, unlike Comparative Example 1, the residual chlorine content is 0.01 mass%, which satisfies the condition for the residual chlorine content (see FIG. 4). However, in manufacturing the positive electrode mixture paste, the positive electrode conductive agent, the positive electrode solvent, the positive electrode binder, and the positive electrode active material are charged and kneaded at once. This leads to molecular chain scission of the positive electrode binder PVdF during kneading. The adhesion index is 0.83, which exceeds 0.80. As a result, good results are obtained for both the paste viscosity and the filter clogging, with a score of "◯", but the peel strength remains "△", although it is improved from Comparative Example 1.

[0070] Comparative Example 3 In Comparative Example 3, the positive electrode mixture paste is produced through a first kneading step S21 to a third kneading step S23 (see FIG. 5). In Comparative Example 3, the amount of residual chlorine is 0.025% by mass, which exceeds 0.02% by mass. Therefore, the positive electrode binder is too entangled with the positive electrode active material, and the paste viscosity becomes high. As a result, the adhesion index falls below 0.70. Therefore, the paste viscosity is rated as "x", and the filter clogging is also rated as "△". Although the peel strength is improved compared to Comparative Example 1, it remains rated as "△".

[0071] Comparative Example 4 In Comparative Example 4, the positive electrode mixture paste is produced through a first kneading step S21 to a third kneading step S23 (see FIG. 5). However, the amount of residual chlorine is 0.001% by mass, which is smaller than 0.002% by mass, and the positive electrode binder PVdF is not sufficiently entangled with the positive electrode active material. For this reason, the adhesion index is 0.82, which exceeds 0.80. As a result, the paste viscosity and the filter clogging are both good results of "◯", but the peel strength is "△".

[0072] Comparative Example 5 In Comparative Example 5, the positive electrode mixture paste is produced through a first kneading step S21 to a third kneading step S23 (see FIG. 5). However, the amount of excess lithium is 0.13 mass %, exceeding 0.12 mass %. This results in a high paste viscosity. As a result, the paste viscosity is rated "x" and the filter clogging is rated "△". The peel strength is rated "△".

[0073] Comparative Example 6 In Comparative Example 6, a positive electrode mixture paste is produced through a first kneading step S21 to a third kneading step S23 (see FIG. 5). However, the amount of excess lithium is 0.065 mass%, which is less than 0.07 mass%. The adhesion index is 0.82, which exceeds 0.80. Therefore, the paste viscosity and the filter clogging are both good results of "◯", but the peel strength is "△".

[0074] Comparative Example 7 In Comparative Example 7, the positive electrode mixture paste is produced through the first kneading step S21 to the third kneading step S23 (see FIG. 5). Furthermore, the amount of residual chlorine and the amount of excess lithium are both within a predetermined range. However, the kneading time in the third kneading step S23 is shorter than the specified time, resulting in insufficient kneading. As a result, the solubility index is 1.13, which is lower than 1.19. In this case, the positive electrode mixture paste contains residual PVdF, which is the positive electrode binder. For this reason, the paste viscosity is rated as "△", and both the filter clogging and peel strength are rated as "×".

[0075] In contrast, in Examples 1 to 5, the positive electrode mixture paste is produced through a first kneading step S21 to a third kneading step S23 (see FIG. 5). The residual chlorine content is 0.002 mass% or more and 0.02 mass% or less, the excess lithium content is 0.07 mass% or more and 0.12 mass% or less, the solubility index is 1.19 or more, and the adhesion index is 0.7 mass% or more and 0.80 or less. Therefore, in Examples 1 to 5, the paste viscosity, filter clogging, and peel strength are also rated as "good."

[0076] [Effects of the embodiment] The above-described embodiment can provide the following advantages. (1) In the second kneading step S22, it is possible to prevent the molecular chain of the positive electrode binder from being cut when the positive electrode conductive agent is dispersed. In the third kneading step S23, the remaining positive electrode binder is added and kneaded to obtain the required peel strength.

[0077] The positive electrode mixture layer can increase the peel strength by increasing the amount of the positive electrode binder added. On the other hand, the positive electrode binder has a high resistance itself, so that the internal resistance is high. In the present invention, the adhesion between the positive electrode active materials is also increased, and the positive electrode binder can be sufficiently dissolved in a positive electrode solvent such as NMP. Therefore, the peel strength of the positive electrode active material can be further increased while suppressing the amount of the positive electrode binder added. In addition, since the positive electrode mixture paste has an appropriate viscosity, problems such as filter clogging and streaking during the coating process can be suppressed.

[0078] (2) In the first kneading step S21, the chlorine component contained in the positive electrode active material attracts the positive electrode binder, such as PVdF, to the positive electrode active material, thereby entangling the positive electrode active material and the positive electrode binder. If the chlorine content of the positive electrode active material is less than 0.002% by mass with respect to the mass of the positive electrode active material, the effect of entangling the positive electrode binder and the active material cannot be sufficiently obtained. If the chlorine content is more than 0.02% by mass with respect to the mass of the positive electrode active material, the viscosity of the positive electrode mixture paste becomes too high, causing filter clogging, streaking, and the like in the coating step.

[0079] (3) The excess lithium forms long-chain double bonds through a dehydrofluorination reaction, making it difficult for the positive electrode binder to move from the surface of the active material. If the amount of excess lithium is less than 0.07% by mass relative to the mass of the positive electrode active material, the peel strength becomes insufficient. If the amount of excess lithium is more than 0.12% by mass relative to the mass of the positive electrode active material, the viscosity of the positive electrode mixture paste becomes too high, causing filter clogging and streaking during the coating process.

[0080] (4) The solubility index of the positive electrode solvent increases as the positive electrode binder dissolves. By controlling the solubility index to be 1.19 or more, a positive electrode mixture paste in which the positive electrode binder is sufficiently dissolved can be produced after the third kneading step S23.

[0081] (5) By controlling the adhesion index to be 0.70 or more and 0.80 or less, the dissolution state of the positive electrode binder can be made appropriate. In other words, the peel strength can be maintained while suppressing problems such as filter clogging and streaking during the coating process.

[0082] [Example of change] The above embodiment can be modified as follows: The following modified examples can be combined as long as they are not technically inconsistent.

[0083] The adhesion index may be less than 0.70, or more than 0.80, so long as it is possible to suppress an increase in internal resistance, prevent filter clogging, and maintain peel strength.

[0084] The solubility index may be less than 1.19 as long as it is possible to suppress an increase in internal resistance, prevent filter clogging, and maintain peel strength. The amount of excess lithium contained in the positive electrode active material may be less than 0.07% by mass relative to the mass of the positive electrode active material, or more than 0.12% by mass relative to the mass of the positive electrode active material, so long as it is possible to suppress an increase in internal resistance, suppress filter clogging, and maintain peel strength.

[0085] The chlorine content in the positive electrode active material may be less than 0.002% by mass relative to the mass of the positive electrode active material, or more than 0.02% by mass relative to the mass of the positive electrode active material, so long as it is possible to suppress an increase in internal resistance, suppress filter clogging, and maintain peel strength.

[0086] The positive electrode solvent is not limited to NMP. The positive electrode binder is not limited to PVdF. The positive electrode binder may be, for example, polyvinyl alcohol (PVA) or styrene butadiene rubber (SBR).

[0087] The positive electrode mixture layer 23 may be provided on one surface of the positive electrode substrate 22 . Although the lithium ion secondary battery 10 has been exemplified as a nonaqueous secondary battery, the present invention can be applied to any nonaqueous secondary battery in which the negative electrode active material expands during charging. Also, although a graphite-type material has been exemplified as the negative electrode active material, the present invention can also be applied to nonaqueous secondary batteries using silicon-based negative electrode active materials, since the negative electrode active material expands during charging.

[0088] The lithium ion secondary battery 10 may be mounted on an automatic transport vehicle, a special vehicle for loading and unloading, an electric vehicle, a hybrid vehicle, a computer, or other electronic device, or may be part of other systems. For example, it may be mounted on a moving object such as a ship or an aircraft, or may be a power supply system that supplies power from a power plant via a substation to a building or home in which a secondary battery is installed. [Explanation of symbols]

[0089] 10...Lithium-ion secondary battery 11. Case 11A…Side wall 20...Electrode body 21…Positive electrode plate 21A…Positive electrode inner circumferential surface 21B…Positive electrode outer circumferential surface 22...Positive electrode substrate 23...Positive electrode mixture layer 24…Negative electrode plate 24A…Negative electrode inner circumferential surface 24B…Negative electrode outer surface 25...Negative electrode substrate 26...Negative electrode mixture layer 27…Separator

Claims

1. A method for manufacturing a positive electrode plate including a positive electrode substrate and a positive electrode mixture layer provided on at least one surface of the positive electrode substrate, a positive electrode mixture paste production step of producing a positive electrode mixture paste for forming the positive electrode mixture layer; A coating step of coating the positive electrode mixture paste, The positive electrode mixture paste manufacturing process includes: a first kneading step of kneading a positive electrode active material, a part of the total amount of a positive electrode binder to be added, and a part of the total amount of a positive electrode solvent to be added to produce a first kneaded paste; A second kneading step of producing a second kneaded paste by adding the remainder of the total amount of the positive electrode solvent and the positive electrode conductive agent to the first kneaded paste and kneading them; and a third kneading step of adding the remainder of the total added amount of the positive electrode binder to the second kneaded paste and kneading the mixture to produce the positive electrode mixture paste. A method for manufacturing a positive electrode plate.

2. The positive electrode binder is polyvinylidene fluoride (PVdF). The method for producing the positive electrode plate according to claim 1 .

3. The positive electrode solvent is an NMP (N-methyl-2-pyrrolidone) solution. The method for producing a positive electrode plate according to claim 1 or 2.

4. The positive electrode active material contains a chlorine component, The chlorine content of the positive electrode active material is 0.002 mass % or more and 0.02 mass % or less with respect to the mass of the positive electrode active material. The method for producing the positive electrode plate according to claim 1 .

5. The amount of excess lithium contained in the positive electrode active material is 0.07% by mass or more and 0.12% by mass or less with respect to the mass of the positive electrode active material. The method for producing the positive electrode plate according to claim 1 .

6. A solubility index calculated by (DCR of the positive electrode solvent in the positive electrode mixture paste after the third kneading step) / (DCR of the positive electrode solvent in the second kneaded paste before the start of the third kneading step) is 1.19 or more. The method for producing the positive electrode plate according to claim 1 .

7. An adhesion index calculated by (DCR of the positive electrode active material in the positive electrode mixture paste) / (DCR of all components of the positive electrode active material, the positive electrode conductive agent, and the positive electrode solvent in the positive electrode mixture paste) is 0.70 or more and 0.80 or less. The method for producing the positive electrode plate according to claim 1 .

Citation Information

Patent Citations

  • Lithium ion secondary battery

    JP2012134023A